Structural Model to Predict Satisfaction and Performance Users of SIKD at Government Organizations in South Kalimantan - Fahrianta, Riswan Yudhi; Chandrarin, Grahita; Subiyantoro, Edi (Jurnal Pekommas, 2021)
The successful adoption of ICT by local governments still requires evaluation because of several issues related to the use and utilization of the SIKD. The variety of SIKD applications, limited server, and network capacity, limited human resource personnel, and lack of technical guidance because regulatory changes put pressure on user satisfaction and performance. Academic evaluation of SIKD adoption from the user's perspective is needed to explore advanced concepts of e-government development. The research model was analyzed with the Partial Least Square (SEM-PLS) approach. The results showed the perceived usefulness, perceived ease of use, subjective norms, and facilitating conditions influenced user satisfaction and subsequently, user satisfaction affected user performance. The conceptual framework tested in this study was able to show that under conditions of ICT mandatory use by organizations, behavioral beliefs influence user satisfaction and have an important impact on user performance.